Tantangan Implementasi Hukum Potong Tangan Pencuri di Indonesia: (Tela’ah Intrpretasi Dengan Pendekatan Hermenutika Fazlur Rahman) - Mubarok, Mohammad Nabil Iklil; Saichul Anam (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
This article aims to examine the interpretation of Q.S. Al-Mā’idah (5): 38 regarding the cutting off of hands from Fazlur Rahman’s perspective. Specifically, this research focuses on the context of Indonesia as the main study area. Rahman is a contemporary Islamic thinker who introduced a groundbreaking approach to reading and understanding the Qur’an in line with modern contexts. His thought process is known as the Double Movement. The method employed in this article is qualitative, utilizing library studies. The analyzed data is presented in the form of descriptive narrative. This study identifies two significant findings: first, from the perspective of the ratio legis, the purpose of the hand-cutting verse is deterrence. Second, in the context of Indonesia, the punishment of cutting off hands is replaced with imprisonment, which appears to be more humane.